Stent strength improvement through the utilization of selective laser melting technology - Omar, Mohd Asnawi (2021)
The invention of Metal Additive Manufacturing or known as Selective Laser Melting has opened a wide application of field such as biomedical devices, automotive and Oil & Gas, Aerospace and Consolidation of parts, and in certain area where stronger parts can be produced. Furthermore, the Selective Laser Melting (SLM) has been known to produce new net shape and intricate design which cannot be achieved through conventional processing. In this research, the problem statement of laser cuts stent has been addressed to overcome the constraint of laser cutting by enhancing with the SLM technology. The additively manufactured stent is consisting of seven (7) type design where the purpose was manufacturability through SLM technology by utilizing the strut, diameter, height, and angle. A set of default parameter with the laser power of 200 Watt, with the hatching distance of 0.14mm, layer thickness of 0.02mm and scanning speed of 800mm/s has been applied through a series of different type of additive stent. The tolerances or shrinkage of the stent are also achieving a good result because the dimensional accuracy reaches closely to 0.5% shrinkage (±70 μm) of diameter and 0.03% (±30 μm) for the height. Result from testing method also shown that, where all seven (7) AM stents showed better performance compared with conventional stent due to the placement of strut hoops in all connectors with highest stiffness was 1.44 N/mm (in axial) and 0.75 N/mm in radial during compression load. Whereas the flexural test showed a better stiffness in the value of 0.44N/mm. The heat treatment stent was then compared with the As-built stent where there is significant increase on compression test (2.04 N/mm). While the Flexural Test showed the decrease of stiffness (0.36 N/mm), but still the acceptance rate was better compared to the commercial stent in the market. The Clinical test (Cytotoxicity test) also showed promising result where all the additively manufactured stent showed 100.3% viability cells.